Mitigation of Calcium-Related Disorders in Soilless Production Systems - Virginia Birlanga; José Ramón Acosta-Motos; José Manuel Pérez-Pérez (Agronomy, 2022)
In the current scenario of human-driven climate change, extreme weather events will likely affect agricultural production worldwide. Soilless production systems have recently arisen as a solution to optimize the use of natural resources, such as water and soil, and hence will contribute to reducing the environmental impact of agriculture. However, nutritional imbalance due to adverse environmental factors, such as drought, high temperatures, and salinity, might produce calcium-related physiological disorders during plant growth, such as blossom-end rot (BER) in fruits and tipburn (TB) in leaves, which are a serious problem in crop production. Here, we discuss the different agronomic, physiological, and genetic factors that favor the induction of BER in tomato and TB in lettuce and anticipate the use of an integration of breeding and technological approaches to alleviate nutritional disorders in soilless production systems.